Lymphocyte-to-Monocyte Ratio is Associated with the Poor Prognosis of Breast Cancer Patients Receiving Neoadjuvant Chemotherapy - Ma Y; Zhang J; Chen X (Cancer Management and Research, 2021)
Youzhao Ma, Jingyang Zhang, Xiuchun Chen Department of Breast Disease, Henan Breast Cancer Center, Affiliated Cancer Hospital of Zhengzhou University & Henan Cancer Hospital, Zhengzhou, 450008, People’s Republic of ChinaCorrespondence: Xiuchun ChenDepartment of Breast Disease, Henan Breast Cancer Center, Affiliated Cancer Hospital of Zhengzhou University & Henan Cancer Hospital, No. 127, Dongming Road, Zhengzhou, 450008, People’s Republic of ChinaEmail cxc701024@163.comPurpose: Systemic inflammatory cell ratio, neutrophil–lymphocyte ratio (NLR), platelet–lymphocyte ratio (PLR), and lymphocyte–monocyte ratio (LMR) are used as prognostic indicators for several types of tumors. The purpose of this study was to evaluate the predictive value of inflammatory markers for pathological response and prognosis in breast cancer patients receiving neoadjuvant chemotherapy (NAC).Methods: In this study, we collected data of 203 breast cancer patients who underwent surgery after receiving standard neoadjuvant therapy. The effects of NLR, PLR, and LMR on the disease-free survival (DFS) of patients with breast cancer were analyzed by χ2 test and Cox regression analyses.Results: We found that 27 of the 203 patients (13.3%) had local or distant metastases. The peripheral blood NLR, PLR, and LMR areas under the curve (AUC) were 0.674 (0.555– 0.793), 0.630 (0.508– 0.753), and 0.773 (0.673– 0.874), respectively. The optimal cutoff values were 3.0, 135, and 6.2, respectively. Univariate and multivariate analyses revealed that LMR was related to the pathological complete response (pCR) rates and breast cancer DFS (P < 0.05). Among all patients, those with low LMR, HER-2 positive, and lymph node status (N2– 3) demonstrated poor DFS.Conclusion: Our study thus demonstrated that LMR can act as a potential marker for predicting the efficacy and prognosis of patients with breast cancer.Keywords: breast cancer, platelet-lymphocyte ratio, neutrophil–lymphocyte ratio, lymphocyte–monocyte ratio, disease-free survival